A case of fusional vergence disorder associated with myopia - Biswas, Vishal; Majumder, Roshni (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
Aim: This case study demonstrates the management options for fusional vergence dysfunction (FVD) and uncorrected myopia. Background: Binocular vision disorder with abnormalities in fusional vergence dynamics is referred to as “fusional vergence dysfunction (FVD).” A patient with FVD has asthenopic symptoms, no refractive error, healthy eyes, normal accommodative functions, a normal accommodative convergence/accommodation ratio, and normal distant and near phoria status. Case presentation: A 19-year-old female diagnosed to have FVD along with simple myopia presented to the clinic with a complaint of asthenopic symptoms. Complete vergence-related and accommodation-related vision therapies were advised and provided. After 2 months from the initial presentation, the patient successfully recovered from the existing condition. Conclusion: Uncorrected myopia with FVD was determined based on the patient’s complaint and the results of the examination. The condition was treated with vision therapy and a distance optical correction. An office-based and home-based program can successfully cure FVD.